Crystal structure, Hirshfeld surface analysis and crystal voids of 4-nitrobenzo[c][1,2,5]selenadiazole - Atash V. Gurbanov; Tuncer Hökelek; Gunay Z. Mammadova; Khudayar I. Hasanov; Tahir A. Javadzade; Alebel N. Belay (Acta Crystallographica Section E: Crystallographic Communications)
The title molecule, C6H3N3O2Se, is almost planar. In the crystal, intermolecular C—H...O hydrogen bonds link the molecules into a network structure, enclosing R22(7) and R33(8) ring motifs, parallel to the bc plane. There are π–π interactions present with centroid-to-centroid distances of 3.746 (3) and 3.697 (3) Å. A Hirshfeld surface analysis of the crystal structure indicates that the most important contributions for the crystal packing are from H...O/O...H (19.6%), H...N/N...H (11.0%), H...Se/Se...H (8.5%), O...Se/Se...O (8.2%), H...H (7.4%), C...N/N...C (7.3%) and N...Se/Se...N (7.2%) interactions. Hydrogen bonding and van der Waals interactions are the dominant interactions in the crystal packing. The volume of the crystal voids and the percentage of free space were calculated to be 25.60 Å3 and 3.73%, showing that there is no large cavity in the crystal.